THE POSITION OF THE TROBAIRITZ IN MEDIEVAL SOCIETY - Rashidova, Laura (Журнал иностранных языков и лингвистики, 2021)
Written sources reveal how these female poets were seen in a very different context from the one in which they developed. In fact, a beloved woman becomes a fan who, from the arrogant spirit that she was, becomes the humble servant of the one she loves and of whom she sings. The “domna” becomes “prejador”, the “ricor” and the “merce” become male privileges. This long-observed paradox has remained unsolved. They were high society ladies who also wanted to openly express their feelings and emotions, as was allowed for men.